FAKTOR PENENTU NIATAN UNTUK MEMBELI KEMBALI SECARA ONLINE: SUATU INTEGRASI ANTESEDEN FAKTOR KEPERCAYAAN DAN KEPUASAN - Jeniwanti Carolina Kotte (Jurnal Riset Manajemen dan Bisnis, 2017)
This study aims to examine the factors that determine the intention to buy back online throughantesenden integration of trust and satisfaction. The object of this study is they who uses the servicesonline stores. Data were collected through an online questionnaire, distributed to the public whoactually use the online store site. 190 data were collected. Data analysis using Structural EquationModeling (SEM) to test the hypothesis with the help of application lisrel 8.80. The results showed thatthe perception of security no positive effect on customer confidence, while the perception of privacypositive effect on confidence. Perception of ease of use is not a positive influence to the customer'ssatisfaction and trust no positive effect on repurchase intention. Future studies are necessary toexamine the situation before and after doing shopping online in order to learn the extent of thecustomer's intentions to buy back. Lastly, the findings in this study are expected to provide a usefulguide for practitioners and researchers.Keywords: Trust, satisfaction, intent to repurchase, TAM